Procurement and Evaluation of Hepatocytes for Transplantation From Neonatal Donors After Circulatory Death. (January 2022) - Bluhme, Emil; Henckel, Ewa; Gramignoli, Roberto; Kjellin, Therese; Hammarstedt, Christina; Nowak, Greg; Karadagi, Ahmad; Johansson, Helene; Jynge, Öystein; Söderström, Maria; Fischler, Björn; Strom, Stephen; et al.
Hepatocyte transplantation is a promising treatment for liver failure and inborn metabolic liver diseases, but progress has been hampered by a scarcity of available organs. Here, hepatocytes isolated from livers procured for a neonatal hepatocyte donation program within a research setting were assessed for metabolic function and suitability for transplantation. Organ donation was considered for infants who died in neonatal intensive care in the Stockholm region during 2015–2021. Inclusion was assessed when a decision to discontinue life-sustaining treatment had been made and hepatectomy performed after declaration of death. Hepatocyte isolation was performed by three-step collagenase perfusion. Hepatocyte viability, yield, and function were assessed using fresh and cryopreserved cells. Engraftment and maturation of cryopreserved neonatal hepatocytes were assessed by transplantation into an immunodeficient mouse model and analysis of the gene expression of phase I, phase II, and liver-specific enzymes and proteins. Twelve livers were procured. Median warm ischemia time (WIT) was 190 [interquartile range (IQR): 80–210] minutes. Median viability was 86% (IQR: 71%–91%). Median yield was 6.9 (IQR: 3.4–12.8) x10 6 viable hepatocytes/g. Transplantation into immunodeficient mice resulted in good engraftment and maturation of hepatocyte-specific proteins and enzymes. A neonatal organ donation program including preterm born infants was found to be feasible. Hepatocytes isolated from neonatal donors had good viability, function, and engraftment despite prolonged WIT. Therefore, neonatal livers should be considered as a donor source for clinical hepatocyte transplantation, even in cases with extended WIT.